Justificación de la aplicación práctica de la procalcitonina en adultos sépticos hospitalizados: revisión bibliográfica. - Diaz Orellana, Allison Michelle; Patiño Pineda, Carlos Paul (My University, 2024)
Introduction: Procalcitonin (PCT) is a protein precursor of the hormone calcitonin, has become a promising biomarker for assessing the presence of bacterial infections and severity in patients with sepsis; the Infectious Diseases Society of America refers that procalcitonin is useful for differentiating the causative agent of infection, being useful for monitoring but not for therapeutic employment. Objective: To establish the practical application of procalcitonin in hospitalized septic patients with bacterial etiology by means of a bibliographic review for the use of antibiotic therapy. Methodology: Research with positivist paradigm of quantitative approach, basic type, non-experimental design, documentary modality and interpretative methodology, applying inclusion criteria and Boolean operators to a total of 60 bibliographic reviews from Pubmed, Elsevier and Scielo using PRISMA methodology. Results and Discussion: There is a practical application of PCT in hospitalized septic patients, this was evidenced by the fact that most of the patients underwent a PCT test at the beginning of their hospital stay, finding its usefulness for antibiotic management; however, no guidelines were found to justify its use. Conclusion: it is evident that there is no justification for the practical application of procalcitonin in the management of the septic patient, its usefulness is little and it is scarcely demonstrated, however, the inclinations of its use are various and more studies are required to be able to issue a clear position on its usefulness.
Introducción: La procalcitonina (PCT) es una proteína precedente de la hormona calcitonina, se ha convertido en un biomarcador prometedor para evaluar la presencia de infecciones bacterianas y la gravedad en pacientes con sepsis; la Sociedad de enfermedades infecciosas de América refiere que la procalcitonina es útil para diferenciar el agente causal de la infección, siendo útil para la monitorización más no para el empleo terapéutico. Objetivo: Establecer la aplicación práctica de la procalcitonina en pacientes sépticos hospitalizados de etiología bacteriana mediante una revisión bibliográfica para el empleo de la terapia antibiótica. Metodología: Investigación con paradigma positivista de enfoque cuantitativo, tipo básico, diseño no experimental, modalidad documental y metodología interpretativa, aplicando criterios de inclusión y operadores booleanos un total de 60 revisiones bibliográficas provenientes de Pubmed, Elsevier y Scielo usando la metodología PRISMA. Resultados y Discusión: Existe aplicación práctica de la PCT en pacientes sépticos hospitalizados, esto se evidenció debido que a la mayoría de los pacientes se les realizó un examen de PCT al inicio de su estancia hospitalaria encontrando su utilidad para el manejo antibiótico sin embargo no se encontraron guías que justifiquen su uso. Conclusión: se evidencia que no existe una justificación de la aplicación práctica de la procalcitonina en el manejo del paciente séptico, su utilidad es poca y se encuentra escasamente demostrada, sin embargo, las inclinaciones de su uso son varias y se requieren más estudios para poder emitir una postura clara sobre su utilidad.
Keywords: POLIPEPTIDO ALFA RELACIONADO CON CALCITONINA; INFECCIONES; BIOMARCADORES; SEPSIS